The blacklist. The complete third season [videorecording (DVD)] - Spader, James; Boone, Megan, 1983-; Klattenhoff, Diego (Sony Pictures Home Entertainment, 2015)
Season Three takes a heart-racing turn when Red and Agent Keen, become fugitives on the run. With Assistant FBI Director Harold Cooper under investigation, Agent Donald Ressler leads the FBI Task Force on the manhunt. As Keen delves deeper into Red's underworld of covert operations, she continues to struggle with self-discovery and her indefinable relationship with Tom. Both Red and Keen are radically challenged personally and professionally.